A Systematic Review with Meta-Analysis on the Effects of Plyometric-Jump Training on the Physical Fitness of Combat Sport Athletes - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
We aimed to assess the athletic performance changes in combat sport athletes (CoSAs) after plyometric-jump training (PJT), compared to control conditions, through a systematic review with meta-analysis. Following PRISMA guidelines, three electronic databases were searched for includable articles, according to a PICOS approach. Using a random-effects model, Hedges’ g effects sizes (ES) were calculated. Heterogeneity was assessed using the I2 statistic, with values of <25%, 25–75%, and >75% representing low, moderate, and high levels of heterogeneity, respectively. Statistical significance was set at p ≤ 0.05. The certainty of evidence was assessed using the GRADE approach. Twelve eligible articles were identified for systematic review, seven of high quality and five of moderate quality, according to the PEDro scale. The studies recruited taekwondo, silat, wrestling, judo, fencing, and karate athletes (292 total participants), including specific–active and active controls. Most participants had a mean age of <18 years and were males (n = 225). Compared to the control, PJT programmes, involving 4–12 weeks and 2–3 sessions per week, induced small to moderate improvements (ES = 0.47 to 1.04) in athletes’ maximal strength (e.g., 1RM squat), vertical jump height, change-of-direction speed, and specific performance (e.g., fencing movement velocity), although without meaningful effects on body mass, fat mass, and muscle mass (ES = 0.02 to −0.06). Most (7 of 8) outcomes attained low heterogeneity. The outcome-level GRADE analysis indicated a certainty of evidence from low to moderate. In conclusion, PJT, when compared to control conditions, may improve CoSA athletic performance. © 2023 by the authors.